CEPHALOMETRIC CHARACTERISTICS OF SKELETAL FORMS OF DISTAL BITE - Kuroiedova, V.D.; Vyzhenko, Ye.Ye.; Stasiuk, О.А.; Sokolohorska-Nykina, Yu.К.; Petrova, А.V. (World of Medicine and Biology, 2022)
The article highlights the results of research on the differential diagnosis of skeletal forms in distal occlusion. Distal occlusion is the most common anomaly of the dental system after Angle class I occlusion pathologies and ranges from 38 % to 65 %. The clinical method was to examine patients with Angle class II dental anomalies. The radiological method consisted of the study of lateral cephalograms of patients with the software “AudaxCeph”. Nine forms of prognostic distal occlusion have been identified based on cephalometric studies. Among all forms, the most common is maxillary prognathism 35.59 %. The values of cephalometric parameters required for the diagnosis of prognostic distal occlusion are essential for clarifying the form of dental anomaly and permit to detail skeletal forms.
Keywords: dental anomaly; upper jaw; lower jaw; prognathism; distal occlusion